ANALYSIS OF HIGH SCHOOL STUDENTS' ERRORS IN SOLVING LINEAR PROGRAMMING STORY PROBLEMS BASED ON NEWMAN'S PROCEDURE - Rusli, Nalita; Abidin, Zainal; Yani, Muhammad (Al-Khawarizmi, 2024)
Error analysis based on Newman's procedure helps students understand the types of mistakes they make, thereby enabling them to anticipate and minimize these errors. This research aims to identify the errors high school students make in solving linear programming story problems and the factors causing these errors based on Newman's procedure. The study employs a qualitative approach with a descriptive method. The subjects consist of four students selected based on the frequency of errors. Data was collected through tests and interviews, then analyzed through data reduction, data presentation, and drawing conclusions. The results indicate that students make errors in understanding the problem, problem transformation, process skills, and final answer writing stages. The types of errors made by students based on mathematical objects include factual errors, conceptual errors, operational skill errors, and principle errors. The causes of these errors are attributed to rushing, physical conditions of students, neglecting steps deemed unimportant, and insufficient time provided to complete the tasks.